A mini-review on release oscillation in a hollow fiber - Lin, Ling; Li, Ya (Frontiers in Physics, 2023)
This mini-review aims at strengthening links among textile science, physics and mathematics, the state-of-art technology for silver ions’ release from hollow fibers is reviewed, its bottleneck problems are spotted, and some open problems are elucidated. The release oscillation opens a new era for modern applications of hollow fibers containing silver ions.